Oxford think! new syllabus Mathematics 3 - Har, Dr Yeap Ban (Karachi : Oxfore university press, 2024)
"Think! New Syllabus Mathematics 3 (8th Edition)" is a mathematics textbook designed for students at the middle school level. The book is part of a series that aligns with the syllabus requirements for students to develop a solid understanding of mathematical concepts.
Keywords: Math : Textbook; Oxford : 8th edition